Lord Home and Anglo–American relations, 1961–1963 - Holt, Andrew (Taylor & Francis (Routledge), 2005)
This article focuses on the role of Lord Home, the British Foreign Secretary, in the conduct of Anglo–American relations between 1961 and 1963. It studies three controversial policy areas: the newly independent states of Laos and the Congo, along with the debate over the decolonisation of British Guiana; the key Cold War issues of Berlin and Cuba; and a variety of nuclear weapons–related matters. It is argued that Home, in constantly striving to maintain the alliance, was more pro-American than Macmillan. He exercised an important restraining and calming influence on the Prime Minister, preventing him from pursuing potentially damaging initiatives. However, the relationship between the two men was strong. Home’s diplomacy usually complimented Macmillan’s interventions and they often worked together.